Low-dose valacyclovir use with preemptive monitoring in kidney transplant recipients with intermediate cytomegalovirus infection risk - VELİOĞLU, ARZU; ARIKAN, İZZET HAKKI; AŞICIOĞLU, EBRU; TUĞLULAR, ZÜBEYDE SERHAN; AKSU, MEHMET BURAK (My University, 2022)
PROP
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; PROPHYLAXISVALGANCICLOVIRVALACICLOVIRPREVENTIONTHERAPYDISEASE; DISEASE